2018
DOI: 10.1016/j.jnucmat.2017.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of thermo-physical properties and annealing of fast neutron irradiated boron carbide

Abstract: Boron carbide is widely used as a neutron absorber in most nuclear reactors, in particular in fast neutron ones. The irradiation leads to a large helium production (up to 10 22 /cm 3) together with a strong decrease of the thermal conductivity. In this paper, we have performed thermal diffusivity measurements and X-ray diffraction analyses on boron carbide samples coming from control rods of the French Phenix LMFBR reactor. The burnups range from 10 21 to 8.10 21 /cm 3. We first confirm the strong decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In particular, the interplay of helium and the point defects created by neutron irradiation, and their mobility, is crucial in order to understand and control the formation of helium bubbles, which ultimately control internal strain [5] and the lifetime of control rods [2].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the interplay of helium and the point defects created by neutron irradiation, and their mobility, is crucial in order to understand and control the formation of helium bubbles, which ultimately control internal strain [5] and the lifetime of control rods [2].…”
Section: Introductionmentioning
confidence: 99%
“…Maruyama et al [3] demonstrated that the thermal conductivity of boron carbide decreases rapidly to 1/3 of the unirradiated value as early as the burnup of ~5×10 26 cap/m 3 , and then further decreases gradually to 1/10 at about 35×10 26 cap/m 3 . Some other neutron irradiation investigations have also verified the abrupt degradation of thermal conductivity of boron carbide at the very beginning of the irradiation process [5][6][7].…”
Section: Introduction mentioning
confidence: 76%
“…It can be deduced simply that 5×10 26 cap/m 3 of neutron captures can only produce 0.455 at% 10 B burnup of the total boron in a fully dense boron carbide pellet, which implies that the boron carbide pellet would endure an extremely high thermal gradient during most of its service life due to the thermal conductivity degradation. The high thermal gradient will result in a large thermal stress in pellets, and thus lead to an extensive cracking [7,8].…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation
“…All in all there are few reasons to suspect that He diffusion mechanism in B 4 C gets modified around the temperature of 800°C. Interestingly, annealings at such temperature of neutronirradiated B 4 C was reported to allow the "healing" of the c cell parameter 45,50,51 . The three publications reporting such results did not put forward a hypothesis on what phenomenon caused this lattice change.…”
Section: Discussion Of He Diffusion and Releasementioning
confidence: 99%